Effects of glycyrrhetinic acid on production performance, serum biochemical indexes, ruminal parameters, and rumen microflora of beef cattle - Wang, Long; Qu, Mingren; Li, Lin; Mei, Wenliang; Zhang, Fengwei; Hu, Ziyu; Li, Geping; Xu, Lanjiao; Liang, Huan (Frontiers in Veterinary Science, 2025)
This research was carried out to assess the impact of supplementing with glycyrrhetinic acid (GA) on production performance, serum biochemical indexes, ruminal parameters, and rumen bacterial flora of beef cattle. Twenty-four Simmental bulls were randomly assigned to two dietary treatments (n = 12 per treatment): the control treatment (basal ration, CON) and the GA treatment (basal ration supplemented with GA at 0.1% DM). After an 87-day feeding trial (7-day adaptation period and 80-day period dedicated to data and sample collection), feces, blood, and rumen fluid samples were collected on day 87. The GA addition significantly increased the average daily gain of beef cattle (p < 0.05). The GA treatment exhibited significantly greater apparent digestibility of crude protein, neutral detergent fiber, and acid detergent fiber than the control treatment (p < 0.05). Total volatile fatty acid concentration, microbial protein concentration, and propionic acid concentration in the rumen fluid were significantly increased by GA addition (p < 0.05). Compared with the control group, the interleukin-4 concentration was significantly higher in GA treatment (p < 0.05). The indices, including operational taxonomic units (OTUs), Sobs, Shannon, Ace, and Chao1, were found to be greater in the GA treatment. At the phyla level, GA addition (p < 0.05) significantly decreased the relative abundance of Bacteroidetes and increased the relative abundance of Firmicutes, while also significantly decreasing the Bacteroidetes:Firmicutes ratios. At the genera level, the relative abundance of Prevotella, NK4A214_group, norank_f_UCG-011, Prevotellaceae_UCG-003, Christensenellaceae_R-7_treatment, Prevotellaceae_UCG-001, norank_f_Bacteroidales_UCG-001, Pseudobutyrivibrio, and Butyrivibrio significantly differed due to GA addition (p < 0.05). Carbohydrate and amino acid transport and metabolism, as well as energy production and conversion, were significantly enriched in the GA treatment (p < 0.05). In summary, the findings indicated that adding glycyrrhetinic acid to the diet could improve growth performance and modify the rumen microbial composition and diversity of beef cattle.